2020
DOI: 10.19166/nc.v7i2.2313
|View full text |Cite
|
Sign up to set email alerts
|

Literature Review: The Effectiveness of Classic Music Therapy Towards Auditory Hallucination in Schizophrenia Patient [Kajian Literatur: Efektivitas Terapi Musik Klasik Terhadap Halusinasi Pendengaran Pada Pasien Skizofernia]

Abstract: <p>Auditory hallucinations are among the most common sensory perception disorder in schizophrenia patient. Patients with auditory hallucinations are often seen talking to themselves and even doing something dangerous. Music therapy is one of the non-pharmacological interventions that have the ability to improve, restore, and maintain physical, mental, emotional, social and spiritual health. This literature is intended to give a deeper article on the effectiveness of classical music therapy on auditory ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Schizophrenia patients with auditory hallucinations will experience discomfort caused by the sounds they hear, so patients will withdraw from the environment and people around them [19]. Therefore, giving classical music therapy in different places, such as in a quiet and bright room, will make the patient feel comfortable and able to interact with other people so that from these activities, the patient becomes active and can divert auditory hallucinations [11,20,21] The use of classical music as a non-pharmacological therapy is also able to increase the brain's information processing capacity.…”
Section: Wayan Candra I Gusti Ayu Ekawati I Ketut Gama (2014)mentioning
confidence: 99%
See 2 more Smart Citations
“…Schizophrenia patients with auditory hallucinations will experience discomfort caused by the sounds they hear, so patients will withdraw from the environment and people around them [19]. Therefore, giving classical music therapy in different places, such as in a quiet and bright room, will make the patient feel comfortable and able to interact with other people so that from these activities, the patient becomes active and can divert auditory hallucinations [11,20,21] The use of classical music as a non-pharmacological therapy is also able to increase the brain's information processing capacity.…”
Section: Wayan Candra I Gusti Ayu Ekawati I Ketut Gama (2014)mentioning
confidence: 99%
“…Patients usually listen to sounds that call them or tell them to do something, so patients who experience auditory hallucinations are often angry, screaming, scared, confused, looking restless, and uneasy [2,5]. Classical music therapy is a relaxation technique and is appropriate for schizophrenia patients who experience auditory hallucinations and can feel calm, decrease aggressive symptoms, control emotions and spiritual development, and help heal psychological disorders [10,18,19]. Music therapy has a calming effect on the patient [19].…”
Section: Wayan Candra I Gusti Ayu Ekawati I Ketut Gama (2014)mentioning
confidence: 99%
See 1 more Smart Citation
“… 4 In Indonesia, it was found that 47.7% of university students experienced mild to severe depression and 27.4% experienced anxiety. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Halusinasi pendengaran merupakan gangguan persepsi sensori yang paling sering dialami pasien dengan skizofrenia. Pasien dengan halusinasi pendengaran sering terlihat bercakap-cakap sendiri, dan bahkan melakukan sesuatu yang membahayakan (Barus & Siregar, 2020). Halusinasi pendengaran adalah mendengar suara atau kebisingan yang kurang jelas ataupun yang jelas, dimana terkadang suara-suara tersebut seperti mengajak bicara klien dan kadang memerintah klien untuk melakukan sesuatu.…”
unclassified